Narrativas de mulheres e a experiência midiatizada: as transformações nas lógicas de viagem a partir do Instagram - Cecconello, Carolina (Universidade do Vale do Rio dos Sinos, 2021)
When we travel and share it on social media, the actions we perform are passing through mediatization. This research proposes to investigate how the media narratives of women traveling alone affect the experiences and decisions of other women. It is also questioned which meanings about the image of women circulate on Instagram. Mediatization was the main guiding theory of our work. Therefore, this research addresses questions about gender representation, experience, circulation, surveillance, self-exposure, visibility and construction of media narratives. The study is of a qualitative type, has a hypothetical deductive and observational character and uses bibliographical and mediatized case study methodologies. Three interviews were conducted, besides the analysis of 30 publications on Instagram and the application of a survey, which gathered more than 160 responses. Therefore, it was possible to identify the different types of affectations that exist in the process between those who travel and share their experience on Instagram, as the experience is transformed into sharing, whether that of those who experience the trip or that of those who observe from a distance. It was also possible to visualize the different meanings that circulate over the image of the woman traveler on the app, and among them, we highlight that of freedom. In addition, the study shows that there is a communication market on the rise.
Keywords: Mulheres que viajam sozinhas; Experiência midiatizada; Narrativas de viagem; Women traveling alone; Mediatized experience; Traveling narratives